ANALISIS PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA DAN COST OF EQUITY CAPITAL: STUDI PENDEKATAN COMPOSITE MEASURE - Shelni Yuvita; Deni Darmawati (Media Riset Akuntansi, Auditing & Informasi, 2013)
The purpose of this study is to observe the effect of audit quality on earningsmanagement and cost of equity capital. Audit quality is measured by the composite measure (variable AQMS), earnings management is measured by the modified Jones model, the cost of equity capital is measured with a modified Ohlson models with random walk. This study uses manufacturing firms for samples during 2010-2012 by using purposive sampling and regression analysis for analyst the data. The results showed that audit quality has a significant effect on earnings management and cost of equity capital, while for the control variables size and leverage, only leverage which has significant effect to cost of equity capital, and the other has no significant effect on earnings management and cost of equity capital.